Molecular Epidemiology of Hantaviruses in the Czech Republic - Zelena, Hana; Strakova, Petra; Heroldova, Marta; Mrazek, Jakub; Kastl, Tomas; Zakovska, Alena; Ruzek, Daniel; Smetana, Jan; Rudolf, Ivo (Emerging infectious diseases, 2019)
During 2008-2018, we collected samples from rodents and patients throughout the Czech Republic and characterized hantavirus isolates. We detected Dobrava-Belgrade and Puumala orthohantaviruses in patients and Dobrava-Belgrade, Tula, and Seewis orthohantaviruses in rodents. Increased knowledge of eco-epidemiology of hantaviruses will improve awareness among physicians and better outcomes of patients.
Keywords: virové geny; RT-PCR; Humans; Kurkino; Phylogeny; orthohantavirus; imunoglobulin G; rodents; Molecular Epidemiology; lidé; patients; zvířata; Hantavirus; molekulární epidemiologie; Seewis virus; Hantavirus Infections; Dobrava; Dobrava-Belgrade virus; fylogeneze; Tula virus; Czech Republic; hantavirové infekce; Puumala virus; protilátky virové; Immunoglobulin M; Antibodies, Viral; imunoglobulin M; Animals; hantavirus; Česká republika; Immunoglobulin G; molecular epidemiology; viruses; Orthohantavirus; Genes, Viral